The differences in I‘Rab in the Quranic verses and their effects on meaning based on the views of al-Shanqitiy / Syed Shahridzan Syed Mohamed - Syed Shahridzan , Syed Mohamed (2020)
The difference in grammatical cases(I’rab) in the holy verses of the Qur'an according to Al-Shanqiti and its effect on the determination of the meaning of the verse is a problem that issues some research questions such as: what is the method used by Al-Shanqiti in the determination of I'rab in verse the Holy Quran, his stand on the differences of I'rab and the effect of the differences towards the determination of the meaning of the interpretation of the Al-Quran Al-Karim. The importance of this study is to explain the meaning supported by the holy verses of the Quran and the explanation of what is meant from the semantic angle of grammar. The method of this study is based on scientific studies in which it involves the steps involved in the journey of the scientific of I'rab Al-Quran knowledge and guided by the principles of critical analysis and evaluation. The purpose of this study explains the methodology used by Shanqiti to explain the position of I'rab verses of the Holy Qur'an and evaluate his stand on the difference in the position of the I’rab verses. Furthermore, this study also examines Shangiti’s commitment towards the determination of the meaning of the Holy Qur'an and his interpretation on the effect of the differences in the position of I'rab. So far, it has been found that no thesis has ever studied this title in the same way as this comprehensive study which begins with the general overview of the study, followed by a detailed discussion and concludes with conclusions and suggestions. It is hoped that this study can be adapted as one of the syllabuses of Al-Quran and Arabic studies in the future. Furthermore, this study assesses the choice (tarjih) of an i’rab position that is influenced by the thought of Shaqiti’s aqeedah, Fiqh(Islamic jurisprudence), Arabic Linguistic(Grammar and Rethoric) and Quranic Tafsir. Amongst others, the findings of the study has found that the importance of I'rab al-Quran's knowledge plays an important role in the preservation of the recitation of the Al-Quran which defines the signs of the case and also defines the meanings of the verse, as I'rab serves as a distinction between meanings. It is not only focused towards mastering the Arabic language; but it is also useful towards the mastery of the other branches of knowledge within the Islamic studies especially within the field of tafseer Al-Quran.